Eksistensi Sosial Mahasiswa di Era Instagram: Analisis Pengaruh Media Sosial terhadap Gaya Hidup dan Perilaku - Nasution, Mhd. Fatih Fauzan; Batubara, Abdul Karim (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to analyze the social existence of students in using Instagram social media on student lifestyle patterns. Social media supports the public, especially students, in accessing information. The Internet, a commonly used technological device, has the potential to create a whole new type of social connection. This study explores the motivation and impact of Instagram use on the lifestyle of university students. Students who are young people who live stylishly use social media as a means of communication. This research uses a qualitative research method with a phenomenological approach and is analyzed with individual phenomenological descriptions in order to get a comprehensive picture. The research subjects were eighth semester students of the Faculty of Communication Sciences at the State Islamic University of North Sumatra. The results showed that students use Instagram to stand out and seek social recognition. The use of Instagram can change mindsets and actions, making some people more creative and interesting, while others continue to show off their possessions, making Instagram a competition arena and the use of Instagram as a medium for student self-existence is due to the lifestyle of students who follow current trends, a sense of wanting to be appreciated and the desire to get recognition by the people around them.